IMPLEMENTASI E-GOVERNMENT MELALUI MEDIA INFORMASI PUBLIK BERBASIS WEBSITE DAERAH di KABUPATEN TEGAL - Ahmad Iqbal Fuadi; Aufarul Marom (Journal of Public Policy and Management Review, 2016)
Now days, there are still many people complaining about about the lack of transparency between government and community. It can happen because the low public awareness to utilize the progress of technology and the lack of socialization government using technology. The internet be a primary needed to the peoples, not only in urban areas even in the region has been a need of. E government through the public information aims to access and disseminate information in the regions and center so as easy the people to will have all information about bureaucracy in the areas. In this research the writers use qualitative with dishub of communication informatics where website tegal distric as an object . The research results show the low level of awareness the peoples in tegal distric. It seen from the number of visitors website as many as 7000-8000 in 2015. And every year can be fluctuative.When compared with the population of productive age in Tegal district, the percentage is still weak, which is only 11% of the population in productive age, amounting to 889 565.